Occupational Therapy For Pregnat Women With Spinal Cord Injury - Fizzotti, Gabriella (British Journal of Healthcare and Medical Research, 2023)
Introduction: In literature, the writings relating to the importance of the sexual sphere of people with disability are limited, with a clear prevalence of male argumentation. The spinal cord injury (SCI) does not change the woman’s reproductive capacity. The profile of the occupational therapist is changing rapidly with changes in health and social care, and scientific and technical developments. The aim of this paper is to identify the perceived service needs of women with SCI during pregnancy. Material and Method: We considered 19 women with traumatic or not traumtic SCI (6 quadriplegic, 10 paraplegic, 3 paraparetic) who have had post lesion pregnances. An extensive questionnaire regarding daily living problems during pregnancy. was administred via email. Results: Disability could influence the gestational experience: During pregnancy the increasing belly size conditioned moving from the wheelchair to other locations. SCI mothers wanted to know about taking care of newborn baby. Occupational therapist has an important contribution to make to the well-being of SCI woman during the postnatal period. Conclusion: Occupational therapist has an important contribution to make to the well-being of SCI woman during the postnatal period.